Effect Of Educational Intervention on Postgraduates Regarding Bio-Medical Waste Management (BMW) At A Tertiary Care Teaching Hospital, Bhopal - Bathma, Vishal; Agarwal, Sanjay; Sinha, Umesh; Gupta, Girjesh; Khare, Neeraj (National Journal of Community Medicine, 2015)
Introduction: The waste produced in the course of health care activi- ties carries a higher potential for infection and injury than any other type of waste. Objectives: To assess the existing level of knowledge and evaluate the effectiveness of educational intervention and also find out asso- ciation between pre test and post test knowledge score. Methods: An interventional trail was conducted using video lecture and slide show as a tool. Pre and post questionnaire for evaluation was used with scoring. The study was conduct in a tertiary care hos- pital attached to the medical college, in Bhopal. All 1st year PG stu- dents were included in study from different departments. Total 30 PG students were included from all departments. Study was con- ducted in phase manner with objective of imparting knowledge re- garding waste management practices. Results: There was significant increase in knowledge about bio- medical waste management before and after educational intervention which was statistically highly significant (p<0.0001) except symbol of biohazard Conclusion: The knowledge of the 1st year PG medical student re- garding BMW management varied and was not found to be satisfac- tory. The intervention proved to improve their knowledge to signifi- cant level. Training of UG & PG students should be specially empha- sized.